Physiological, transcriptomic, and metabolic analyses reveal that mild salinity improves the growth, nutrition, and flavor properties of hydroponic Chinese chive (Allium tuberosum Rottler ex Spr) - Liu, Ning; Hu, Manman; Liang, Hao; Tong, Jing; Xie, Long; Wang, Baoju; Ji, Yanhai; Han, Beibei; He, Hongju; Liu, Mingchi; Wu, Zhanhui (Frontiers in Nutrition, 2022)
Environmental stressors such as salinity have pronounced impacts on the growth, productivity, nutrition, and flavor of horticultural crops, though yield loss sometimes is inevitable. In this study, the salinity influences were evaluated using hydroponic Chinese chive (Allium tuberosum) treated with different concentrations of sodium chloride. The results demonstrated that lower salinity could stimulate plant growth and yield. Accordingly, the contents of soluble sugar, ascorbic acid, and soluble protein in leaf tissues increased, following the decrease of the nitrate content, under mild salinity (6.25 or 12.5 mM NaCl). However, a higher level of salinity (25 or 50 mM NaCl) resulted in the growth inhibition, yield reduction, and leaf quality deterioration of hydroponic chive plants. Intriguingly, the chive flavor was boosted by the salinity, as evidenced by pungency analysis of salinity-treated leaf tissues. UPLC-MS/MS analysis reveals that mild salinity promoted the accumulation of glutamic acid, serine, glycine, and proline in leaf tissues, and thereby enhanced the umami and sweet flavors of Chinese chive upon salinity stress. Considering the balance between yield and flavor, 12.5 mM is the threshold concentration for NaCl treatments in hydroponic Chinese chive cultivation. Transcriptome analysis revealed that enhanced pungency could be ascribed to a salt stress-inducible gene, AtuFMO1, associated with the biosynthesis of S-alk(en)yl cysteine sulphoxides (CSOs). Furthermore, weighted gene co-expression network analysis (WGCNA) identified that two transcription factors, AtubHLH and AtuB3, were potential regulators of AtuFMO1 expressions under salinity. Thus, these results revealed the molecular mechanism underlying mild salinity-induced CSO biosynthesis, as well as a practical possibility for producing high-quality Chinese chive hydroponically.